When and where do minimum wage hikes increase hours? Evidence from Ireland - Kevin Devereux; Zuzanna Studnicka (University College Dublin, UCD School of Economics, 2023)
Monopsonists suppress employment and wages so as to avoid matching higher wages to their existing employees. Minimum wage hikes force them to pay their existing employees more, reducing the marginal cost of hiring and increasing both wages and employment. However, once the minimum wage exceeds the marginal product of labour, employment effects become negative. We find that the first two National Minimum Wage (NMW) hikes in Ireland over the course of 2016 to 2019 increased hours worked for minimum wage workers (MWWs) in concentrated local labour markets (LLMs), while the third hike had a null or negative effect. MWWs in non-concentrated LLMs and non-MWWs were unaffected. Higher-income, more productive regions drove hours increases, while other regions showed reductions in hours following NMW hikes.
Keywords: 330; Mindestlohn; Beschäftigungseffekt; Arbeitszeit; Irland